A comparative study of Saudi Arabia and Bulgarian Rose oil chemical profile: The effect of the technology and geographic origin. (16th July 2020) - Dobreva, Anna; Getchovska, Kamelia; Nedeltcheva‐Antonova, Daniela
Abstract: The chemical composition and aroma profile of seven Rosa damascena Mill. essential oil samples from Saudi Arabia (Al‐Shafa, Al‐Hada and Al‐Taif area) were studied in details by means of gas chromatography‐mass spectrometry (GC/MS) and gas chromatography with flame ionization detection (GC‐FID). As a result, more than 120 compounds, containing C3 ‐C27 carbon atoms, mainly mono‐ and sesquiterpenoids, were identified by GC/MS. Fifty‐two components with concentration >0.01%, which represents 97.5%‐99.5% of the total detected compounds, were quantified by means of GC‐FID. The main compounds of essential oil samples from Saudi Arabia are as follows: citronellol (19.64%‐28.13%), geraniol (18.29%‐27.23%), nerol (7.02%‐14.27%), linalool (2.93%‐7.55%), β‐phenylethyl alcohol (1.77%‐3.87%) and n‐paraffins (13.53%‐30.85%). An olfactory evaluation of the samples was performed, as well. A sample of Bulgarian Rosa damascena Mill. distilled rose oil was analysed in addition, and its chemical profile and olfactive characteristics were compared to these of the oils from Saudi Arabia. The results for the chemical composition of the rose oil samples allowed revealing the similarity between the samples by using cluster analysis. The Saudi Arabia rose oils, despite do not fully comply with the ISO 9842:2003 standard for rose oil, reveal a high olfactive potential. Abstract : The chemical composition and aroma profile of seven Rosa damascena Mill. essential oil samples from Saudi Arabia were studied in details by means of GC/MS and GC‐FID. An olfactory evaluation of the samples was performed, as well. A sample of Bulgarian Rosa damascena Mill. distilled rose oil was analyzed in addition. The results for the chemical composition of the rose oil samples allowed revealing the similarity between the samples by using cluster analysis.